Career Pathways Programming for Adult Learners in Three U.S. Cities - Esther Prins; Carol Clymer; Sheri Suarez Foreman; Mark Needle; Becky Raymond; Blaire Willson Toso (Adult Education Research Conference, 2018)
This paper presents key findings from a researcher-practitioner partnership that examined career pathways programming among adult education providers in Chicago, Houston, and Miami.
Keywords: adult basic education; career pathways; career technical education; workforce education